FAKTOR DETERMINAN PERDARAHAN POST PARTUM PADA IBU BERSALIN - Nasution, Yulida Effendi; Wulan, Mayang (Nursing Arts, 2023)
According to the World Health Organization (WHO) bleeding while giving birth occupies the highest percentage of causes of maternal death (28%). The aim of the study was to determine the factors associated with post partum bleeding in mothers giving birth at the Pratama Ridho Clinic. The research design used in this study was an analytic survey with a cross sectional approach. The population in this study were 54 mothers who experienced postpartum hemorrhage. The sampling technique uses total sampling where all of the population is taken as a sample of 54 people. Data analysis used univariate analysis (frequency distribution), bivariate (Chi-Square). The results of the bivariate analysis showed that there was a relationship between the age factor (p_value = 0.004), the parity factor (p_value = 0.001), the birth spacing factor (p_value = 0.002) and post-partum bleeding in women giving birth. In conclusion, the determinant factors for post partum bleeding in mothers giving birth at the Pratama Ridho Clinic are age, parity and pregnancy distance